Humic acid removal using forward osmosis - Siti Nudra Shafinie, Ab Aziz; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; Mohammad, Abdul Wahab (Elsevier, 2025)
Forward osmosis (FO) is an emerging membrane separation process that uses osmotic pressure as the driving force for water transport across a semipermeable membrane. Humic acid is a major component of natural organic matter that can cause severe membrane fouling. This chapter presented current research on FO membrane modification to enhance humic acid removal and mitigate fouling. Performance of membranes modified through grafting techniques such as ultraviolet-grafting and chemical grafting using hydrophilic monomers, that is, methacrylic acid (MAA) and N-vinylpyrrolidone (NVP) are discussed. Comparisons on the fouling performance of unmodified and modified polyether sulfone nanofiltration membranes are presented, using humic acid solutions at pH 3 and 7 as model foulants. The modified membranes exhibited lower flux decline and irreversible fouling compared to the pristine membrane. Membranes grafted with NVP showed better antifouling tendency than those grafted with MAA. Rejection of humic acid was also improved by modification under continuous fouling conditions. While further research is needed, tailoring membrane surface chemistry shows promise for controlling humic acid fouling in FO. This could help expand practical applications of FO for wastewater reuse, desalination, and purification of humic-rich waters.